Reorganization Energy upon Controlled Intermolecular Charge‐Transfer Reactions in Monolithically Integrated Nanodevices. Issue 45 (1st October 2021) - Merces, Leandro; Candiotto, Graziâni; Ferro, Letícia Mariê Minatogau; de Barros, Anerise; Batista, Carlos Vinícius Santos; Nawaz, Ali; Riul, Antonio; Capaz, Rodrigo B.; Bufon, Carlos César Bof
Abstract: Intermolecular electron‐transfer reactions are key processes in physics, chemistry, and biology. The electron‐transfer rates depend primarily on the system reorganization energy, that is, the energetic cost to rearrange each reactant and its surrounding environment when a charge is transferred. Despite the evident impact of electron‐transfer reactions on charge‐carrier hopping, well‐controlled electronic transport measurements using monolithically integrated electrochemical devices have not successfully measured the reorganization energies to this date. Here, it is shown that self‐rolling nanomembrane devices with strain‐engineered mechanical properties, on‐a‐chip monolithic integration, and multi‐environment operation features can overcome this challenge. The ongoing advances in nanomembrane‐origami technology allow to manufacture the nCap, a nanocapacitor platform, to perform molecular‐level charge transport characterization. Thereby, employing nCap, the copper‐phthalocyanine (CuPc) reorganization energy is probed, ≈0.93 eV, from temperature‐dependent measurements of CuPc nanometer‐thick films. Supporting the experimental findings, density functional theory calculations provide the atomistic picture of the measured CuPc charge‐transfer reaction. The experimental strategy demonstrated here is a consistent route towards determining the reorganization energy of a system formed by molecules monolithically integrated into electrochemical nanodevices. Abstract : The reorganization energy is defined as the energetic cost to rearrange each chemical species and its surrounding environment when a charge‐transfer reaction occurs. By taking advantage of the most recent progress achieved by the nanomembrane‐origami technology, monolithically‐integrated nanodevices are designed and fabricated to assess the reorganization energy of molecular ultrathin films.